Pedal Proportions of Poposaurus gracilis: Convergence and Divergence in the Feet of Archosaurs. Issue 6 (13th January 2014) - Farlow, James O.; Schachner, Emma R.; Sarrazin, John Cody; Klein, Hendrik; Currie, Philip J.
ABSTRACT The crocodile‐line basal suchian Poposaurus gracilis had body proportions suggesting that it was an erect, bipedal form like many dinosaurs, prompting questions of whether its pedal proportions, and the shape of its footprint, would likewise "mimic" those of bipedal dinosaurs. We addressed these questions through a comparison of phalangeal, digital, and metatarsal proportions of Poposaurus with those of extinct and extant crocodile‐line archosaurs, obligate or facultatively bipedal non‐avian dinosaurs, and ground birds of several clades, as well as a comparison of the footprint reconstructed from the foot skeleton of Poposaurus with known early Mesozoic archosaurian ichnotaxa. Bivariate and multivariate analyses of phalangeal and digital dimensions showed numerous instances of convergence in pedal morphology among disparate archosaurian clades. Overall, the foot of Poposaurus is indeed more like that of bipedal dinosaurs than other archosaur groups, but is not exactly like the foot of any particular bipedal dinosaur clade. Poposaurus likely had a digitigrade stance, and its footprint shape could have resembled grallatorid ichnotaxa, unless digit I of the foot of Poposaurus commonly left an impression. Anat Rec, 297:1022–1046, 2014. © 2014 Wiley Periodicals, Inc.